Sensitivity of SnO2 non-ohmic behavior to the sintering process and to the addition of La2O3 - Oliveira, M. M.; Bueno, Paulo Roberto [UNESP]; Cassia-Santos, M. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2001)
The work reported here consisted of a study of the sensitivity of the nonlinear electrical properties of dense SnO2. CoO ceramic systems to low concentrations of La2O3, sintering temperature and cooling rates. The nonlinear electrical properties of these systems were found to increase with decreasing cooling rates, a behavior attributed to the CoO solid state reactions at temperatures below 1000 degreesC. Post-annealing treatment in N-2-rich atmospheres strongly decreases the non-ohmic behavior of SnO2. CoO ceramic systems. However, this behavior may be restored through thermal treatment in an O-2-rich atmosphere. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: electrical properties; La2O3; sintering; SnO2; varistors